1992
DOI: 10.1007/bf00120750
|View full text |Cite
|
Sign up to set email alerts
|

Gust and downward momentum transport in the atmospheric surface layer

Abstract: The intermittent structure of the turbulent wind field in the atmospheric surface layer is investigated by conditional sampling methods. The results show that downward momentum can be transported efficiently during a peak gust. The horizontal structure of the gust is also revealed by observing the spatial structure of wind speed fluctuations from a network of 28 anemometers. The high wind region consists of a gust front with a sudden increase of wind speed at the front and a slow decrease to its rear. The deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Figure 1 should make this clear. This definition is consistent with the widely reported fact that gusts usually take the form of a sudden increase in wind speed followed by a gradual decrease (see, for example, Hayashi, 1992). It also allows computer processing of the data to identify gusts.…”
Section: Datasupporting
confidence: 86%
“…Figure 1 should make this clear. This definition is consistent with the widely reported fact that gusts usually take the form of a sudden increase in wind speed followed by a gradual decrease (see, for example, Hayashi, 1992). It also allows computer processing of the data to identify gusts.…”
Section: Datasupporting
confidence: 86%
“…Small-scale structures known as microfronts (Gao et al 1989(Gao et al , 1992Mahrt and Howell 1994) or gust fronts (Hayashi 1992) have been found in field experiments investigating turbulence in the surface layer. Microfrontal structures were observed also from low-level aircraft flights (Mahrt 1991), such structures containing distinct high-speed regions, representing certain types of coherent structures in the ABL.…”
Section: Introductionmentioning
confidence: 98%
“…Field experiments in the ABL have resolved turbulence structures called microfronts (Gao et al 1989(Gao et al , 1992 or gust fronts (Hayashi 1992), structures that are small-scale frontal structures containing distinct high-speed regions. Under near-neutral conditions at levels within and above a forest canopy, Gao et al (1989) reported a flow structure consisting of a weak ejection (the region of upward motion) from the canopy top followed by a strong sweep (the region of downward motion) into the canopy.…”
Section: Introductionmentioning
confidence: 99%
“…The sweep transports dry air into the canopy and forms a microfront in the humidity field. Hayashi (1992) observed the horizontal structure of wind speed fluctuations in the surface layer with a network of anemometers, revealing a gust front at the forward edge of the high-speed region. These structures are considered to represent certain types of coherent structures in the ABL.…”
Section: Introductionmentioning
confidence: 99%